Review and Analyze the Sources, Characteristics and Composition of Electronic Waste - N. H. T. Ly; N. T. Giao (Journal of Applied Sciences and Environmental Management)
The objective of this paper was to review and analyze the sources, characteristics and composition of electronic wastes by collecting the studies related to the research problem from various databases. The results of the evaluation of articles show that electronic waste includes all old or expired electrical and electronic equipment that has been discarded by consumers. With an average growth rate of about 2.6 million tonnes per year, it is estimated that by 2030, the amount of e-waste generated will be up to 82 million tonnes. E-waste is classified into many different categories and contains many valuable materials that can be recovered and reused to overcome the shortage of raw materials, while limiting the adverse impacts of hazardous substances in e-waste on the environment and human health. The results of the research provide a general and valuable overview of the sources, characteristics and composition of electronic waste.